Circadian and Plastid Signaling Pathways Are Integrated to Ensure Correct Expression of the CBF and COR Genes during Photoperiodic Growth. Issue 2 (14th April 2016) - Norén, Louise; Kindgren, Peter; Stachula, Paulina; Rühl, Mark; Eriksson, Maria E.; Hurry, Vaughan; Strand, Åsa
Abstract : HSP90, ZTL, PRR5 and HY5 integrate circadian and plastid signaling pathways to regulate CBF and COR expression. Abstract: The circadian clock synchronizes a wide range of biological processes with the day/night cycle, and correct circadian regulation is essential for photosynthetic activity and plant growth. We describe here a mechanism where a plastid signal converges with the circadian clock to fine-tune the regulation of nuclear gene expression in Arabidopsis ( Arabidopsis thaliana ). Diurnal oscillations of tetrapyrrole levels in the chloroplasts contribute to the regulation of the nucleus-encoded transcription factors C-REPEAT BINDING FACTORS (CBFs). The plastid signal triggered by tetrapyrrole accumulation inhibits the activity of cytosolic HEAT SHOCK PROTEIN90 and, as a consequence, the maturation and stability of the clock component ZEITLUPE (ZTL). ZTL negatively regulates the transcription factor LONG HYPOCOTYL5 (HY5) and PSEUDO-RESPONSE REGULATOR5 (PRR5). Thus, low levels of ZTL result in a HY5- and PRR5-mediated repression of CBF3 and PRR5-mediated repression of CBF1 and CBF2 expression. The plastid signal thereby contributes to the rhythm of CBF expression and the downstream COLD RESPONSIVE expression during day/night cycles. These findings provide insight into how plastid signals converge with, and impact upon, the activity of well-defined clock components involved in circadian regulation.